Digitalisasi Pembelajaran Alat Praktikum Fisioterapi melalui Pengenalan Website Physio.Learn - Chaerul Fadly Mochtar; Arimbi; Sarifin; Rusli; Mochtar Luthfi; Rahmat Hidayat Abbas; Abhista Ibnu Fauzan; Sri Wahyuni; Nur Rahma; Alifiah Aisyah Biyni; Syavira Hafis (Journal Social Science And Technology For Community Service, 2025)
Physiotherapy education required optimal mastery of psychomotor skills, yet conventional learning was often hampered by limitations in time, access, and practical equipment demonstration. This activity aimed to improve students’ literacy and skills in using physiotherapy equipment through the socialization of the Physio.Learn website, which featured educational videos. The implementation method employed an educational-participatory approach conducted online, consisting of material preparation, socialization via Zoom, website demonstration, interactive discussion, and feedback evaluation. A total of 139 Physiotherapy students from Universitas Negeri Makassar participated in this activity. Survey results indicated that 72.1% of participants rated the video explanations as “clear” to “very clear,” 83% found the visualizations highly helpful, and 92.4% perceived the videos as beneficial in enhancing understanding. Ease of access and website design were also positively rated by the majority of respondents. These findings reinforced evidence that the integration of digital media based on educational videos effectively improved students’ understanding and skills in using physiotherapy equipment, while promoting more flexible and participatory independent learning. The development of interactive features and improvement of content quality were recommended for future platform optimization.